Cancer survivors' exercise beliefs, knowledge, and behaviors: An Australian National Survey. Issue 6 (30th January 2022) - Caperchione, Cristina M.; Stolp, Sean; Phillips, Jane L.; Agar, Meera; Sharp, Paul; Liauw, Winston; Harris, Carole A.; McCullough, Susan; Lilian, Ruth
Abstract: Aims: This study aimed to (1) explore the perceptions of people living with cancer about exercise in general and exercise as an adjunct form of cancer care, (2) explore their perceptions regarding exercise counselling needs and preferences, and (3) investigate how these perceptions of exercise as an adjunct form of cancer care shape survivors exercise levels postcancer diagnosis. Methods: A cross‐sectional design and online survey were used to recruit cancer survivors via cancer‐related networks throughout Australia. Two factor analyses were conducted to examine the structure and reduce the number of variables pertaining to exercise during and after the cancer treatment. Extracted components were used in one‐way analysis of variance to compare differences in physical activity levels postcancer diagnosis. Results: Participants ( N = 288) had very positive perceptions of exercise, yet only 50% of participants would prefer to receive exercise counselling. Those who were more active postcancer diagnosis had higher exercise beliefs than those who were similarly active ( p = 0.04, r = 0.27) and less active ( p = 0.03, r = 0.24) postdiagnosis. Those who were less active also had lower exercise knowledge than those who were similarly active ( p = 0.01, r = 0.31) and more active ( p = 0.03, r = 0.26). Safety beliefs did not significantly differ between cancer survivors' activity levels ( p = 0.16) Conclusion: This survey highlights the potential benefits of a concentrated effort in connecting survivors to relevant services and resources, and utilizing cancer clinicians to communicate with survivors about the role of exercise in cancer care.